Dune: prophecy. The complete first season [videorecording (DVD)] - Ademu-John, Diane, 1969-; Schapker, Alison, 1971- (Warner Bros. Entertainment Inc., 2025)
Set 10,000 years before the ascension of Paul Atreides, Dune: Prophecy follows two Harkonnen sisters as they combat forces that threaten the future of humankind, and establish the fabled sect that will become known as the Bene Gesserit. Dune: Prophecy is inspired by the novel Sisterhood Of Dune, written by Brian Herbert and Kevin J. Anderson.